Quantifying the success of prey crypsis, aposematism, and evasiveness in avoiding predator attack - Daniel Linke; Jacqueline Hernandez Mejia; Valery N. P. Eche Navarro; Prapti Gohil; César Ramírez García; Letty Salinas; Marianne Elias; Pável Matos‐Maraví (Ecology, 2025)
Antipredator defenses typically act at distinct stages of the predation sequence—encounter, identification, approach, and subjugation. However, their effectiveness has rarely been quantified and compared simultaneously in wild predator–prey systems. We conducted a study in Peru, where we installed aviaries at two localities and recorded the responses of wild avian predators to three types of antipredator defenses—crypsis, aposematism, and evasiveness—expressed by three butterfly prey types. The study included both immature and adult birds from forest and urban environments, representing the present community of insectivorous birds. We tested the theoretical expectations that cryptic butterflies (Nymphalidae: Euptychiina) were rarely detected, aposematic Heliconius (Nymphalidae: Heliconiinae) were often sighted but seldom attacked, and evasive Spicauda (Hesperiidae: Eudaminae) were frequently detected and attacked but evaded capture at higher rates. Despite these distinct defensive strategies, mortality rates among prey types were largely similar, but predator life stage strongly influenced defense effectiveness, with immature birds tending to attack Heliconius more frequently. Additionally, predator family influenced predation patterns, with more skilled insectivores (e.g., Vireonidae) showing higher capture success against defended prey. These findings illuminate the evolutionary pressures that shape predator behavior and prey defenses in tropical ecosystems. The similar mortality rates underscore the adaptive value of these defenses, which collectively distribute the total predation pressure across prey species.

Seasonally recurring patterns of dominant Crenothrix spp. in a European alluvial drinking water well: Significance and potential indicator role - Sophia D. Steinbacher; Katarina Priselac; Wolfgang Kandler; Domenico Savio; Julia Vierheilig; René Mayer; Katalin Demeter; Rita B. Linke; Robert L. Mach; Regina Sommer; Gerhard Lindner; Karen Zuser; et al. (Water Research, 2025)

Evaluating the suitability of large-scale datasets to estimate nitrogen loads and yields across different spatial scales - Andrés Felipe Suárez-Castro; Dale M. Robertson; Bernhard Lehner; Marcelo L. de Souza; Michael Kittridge; David A. Saad; Simon Linke; Rich W. McDowell; Mohammad Hassan Ranjbar; Olivier Ausseil; David P. Hamilton (Water Research, 2025)

Assessing the impact of inland navigation on the faecal pollution status of large rivers: A novel integrated field approach - Sophia D. Steinbacher; Ahmad Ameen; Katalin Demeter; David Lun; Julia Derx; Gerhard Lindner; Regina Sommer; Rita B. Linke; Claudia Kolm; Karen Zuser; Martina Heckel; Andrea Perschl; et al. (Water Research, 2024)

Thermoregulatory ability and mechanism do not differ consistently between neotropical and temperate butterflies - Benita C. Laird‐Hopkins; Esme Ashe‐Jepson; Yves Basset; Stephany Arizala Cobo; Lucy Eberhardt; Inga Freiberga; Josh Hellon; Gwen E. Hitchcock; Irena Kleckova; Daniel Linke; Greg P. A. Lamarre; Alex McFarlane; et al. (Global Change Biology, 2023)
Climate change is a major threat to species worldwide, yet it remains uncertain whether tropical or temperate species are more vulnerable to changing temperatures. To further our understanding of this, we used a standardised field protocol to (1) study the buffering ability (ability to regulate body temperature relative to surrounding air temperature) of neotropical (Panama) and temperate (the United Kingdom, Czech Republic and Austria) butterflies at the assemblage and family level, (2) determine if any differences in buffering ability were driven by morphological characteristics and (3) used ecologically relevant temperature measurements to investigate how butterflies use microclimates and behaviour to thermoregulate. We hypothesised that temperate butterflies would be better at buffering than neotropical butterflies as temperate species naturally experience a wider range of temperatures than their tropical counterparts. Contrary to our hypothesis, at the assemblage level, neotropical species (especially Nymphalidae) were better at buffering than temperate species, driven primarily by neotropical individuals cooling themselves more at higher air temperatures. Morphology was the main driver of differences in buffering ability between neotropical and temperate species as opposed to the thermal environment butterflies experienced. Temperate butterflies used postural thermoregulation to raise their body temperature more than neotropical butterflies, probably as an adaptation to temperate climates, but the selection of microclimates did not differ between regions. Our findings demonstrate that butterfly species have unique thermoregulatory strategies driven by behaviour and morphology, and that neotropical species are not likely to be more inherently vulnerable to warming than temperate species.

Probabilistic fecal pollution source profiling and microbial source tracking for an urban river catchment - Julia Derx; H. Seda Kılıç; Rita Linke; Sílvia Cervero-Aragó; Christina Frick; Jack Schijven; Alexander K.T. Kirschner; Gerhard Lindner; Julia Walochnik; Gabrielle Stalder; Regina Sommer; Ernis Saracevic; et al. (Science of The Total Environment, 2023)

Peripartum cardiomyopathy: a global effort to find the cause and cure for the rare and little understood disease - Amy Li; K. Campbell; S. Lal; Y. Ge; A. Keogh; P. S. Macdonald; P. Lau; John Lai; W. A. Linke; J. Van der Velden; A. Field; B. Martinac; et al. (Biophysical Reviews, 2022)
In this review, we present our current understanding of peripartum cardiomyopathy (PPCM) based on reports of the incidence, diagnosis and current treatment options. We summarise opinions on whether PPCM is triggered by vascular and/or hormonal causes and examine the influence of comorbidities such as preeclampsia. Two articles published in 2021 strongly support the hypothesis that PPCM may be a familial disease. Using large cohorts of PPCM patients, they summarised the available genomic DNA sequence data that are expressed in human cardiomyocytes. While PPCM is considered a disease predominately affecting the left ventricle, there are data to suggest that some cases also involve right ventricular failure. Finally, we conclude that there is sufficient evidence to warrant an RNAseq investigation and that this would be most informative if performed at the cardiomyocytes level rather than analysing genomic DNA from the peripheral circulation. Given the rarity of PPCM, the combined resources of international human heart tissue biobanks have assembled 30 ventricular tissue samples from PPCM patients, and we are actively seeking to enlarge this patient base by collaborating with human heart tissue banks and research laboratories who would like to join this endeavour.

Correction to: The Sydney Heart Bank: improving translational research while eliminating or reducing the use of animal models of human heart disease - C. G. dos Remedios; S. P. Lal; A. Li; J. McNamara; A. Keogh; P. S. Macdonald; R. Cooke; E. Ehler; R. Knöll; S. B. Marston; J. Stelzer; H. Granzier; et al. (Biophysical Reviews, 2018)

Trade‐offs in triple‐bottom‐line outcomes when recovering fisheries - Christopher J Brown; Glenn Althor; Benjamin S Halpern; Md Sayed Iftekhar; Carissa J Klein; Simon Linke; Elizabeth C Pryde; Steven Schilizzi; James E M Watson; Becky Twohey; Hugh P Possingham (Fish and Fisheries, 2018)
Almost all environmental management comes at an economic cost that may not be borne equitably by all stakeholders. Here, we investigate how heterogeneity in catch and profits among fishers influences the trade‐off among the triple‐bottom‐line objectives of recovering a fish population, maximizing its economic value and distributing restrictions equitably across fishers. As a case‐study, we examine management reform of an ecologically and economically important coral reef fishery operating within the Great Barrier Reef Marine Park. Using a simulation model, we find that total profitability of the fishing industry is 40% lower if recovery plans are equitable when compared to the most economically efficient plan. However, efficient recovery plans were typically highly inequitable because they required some fishers to cease fishing. Equity was defined according to different norms, and the efficiency loss was greatest when catch losses were shared equally across fishers rather than in proportion to their historical catch. We then varied key social, economic and biological parameters to identify cases when equity and efficient recovery would trade‐off most strongly. Recovery plans could be both efficient and equitable when heterogeneity in fisher's catches and individual catch efficiencies was lower. If fishers were homogenous then equitable plans could have maximal economic efficiency. These results emphasize the importance of considering heterogeneity in individual fishers when designing recovery plans. Recovery plans that are inequitable may often fail to gain stakeholder support, so in fisheries with high heterogeneity we should temper our expectations for marked increases in profits.

The c.29T>C polymorphism of the transforming growth factor beta-1 (TGFB1) gene, bone mineral density and the occurrence of low-energy fractures in patients with inflammatory bowel disease - I. Krela-Kaźmierczak; M. Michalak; A. Wawrzyniak; A. Szymczak; P. Eder; L. Łykowska-Szuber; M. Kaczmarek-Ryś; N. Drwęska-Matelska; M. Skrzypczak-Zielińska; K. Linke; R. Słomski (Molecular Biology Reports, 2017)

The Sydney Heart Bank: improving translational research while eliminating or reducing the use of animal models of human heart disease - C. G. dos Remedios; S. P. Lal; A. Li; J. McNamara; A. Keogh; P. S. Macdonald; R. Cooke; E. Ehler; R. Knöll; S. B. Marston; J. Stelzer; H. Granzier; et al. (Biophysical Reviews, 2017)

Inter-annual and seasonal variability of radial growth, wood density and carbon isotope ratios in tree rings of beech (Fagus sylvatica) growing in Germany and Italy - M. V. Skomarkova; E. A. Vaganov; M. Mund; A. Knohl; P. Linke; A. Boerner; E.-D. Schulze (Trees, 2006)

Gas and fluid venting at the Makran accretionary wedge off Pakistan - U. von Rad; U. Berner; G. Delisle; H. Doose-Rolinski; N. Fechner; P. Linke; A. Lückge; H. A. Roeser; R. Schmaljohann; M. Wiedicke; SONNE 122/130 Scientific Parties; M. Block; et al. (Geo-Marine Letters, 2000)